Exploring new concepts in biomolecular recognition and ligand discovery - Cho, N (2019)
Aptamers are short nucleic acids that can bind with high affinity to a variety of biological targets through shape complementary. However, aptamers composed of natural bases are susceptible to nuclease degradation and have a limited range of intermolecular interactions with their targets. Here we introduce novel modifications at one of the four bases in SELEX libraries to enhance the interaction capabilities of the DNA and thereby broaden the target spectrum. Initially, azidoethoxy and propargylamino groups are introduced to C2′ position of thymidine or C5 position of deoxyuridine with benefits of further conjugation to novel functional groups – such as hydrophobic amino acid side chains to supplement protein-like interaction or halogen substituted modifications to add halogen bonding interaction. By providing the additional interactions that are not available in a canonical nucleic acid aptamer, next-generation aptamers with high target binding affinity and kinetic are anticipated. For their uses in SELEX to discover next-generation aptamer, the acceptance of chemically functionalised triphosphates by DNA polymerase is firstly examined. Base-modified nucleotides are better substrates for DNA polymerases than sugar-modified nucleotides due to the steric gate of the enzyme. Especially, 5-propargylamino-iodotriazole-dUTP (5-ITZ-dUTP), a monomer which can potentially allow aptamers to form halogen bonding interaction is used in SELEX. Promisingly, a G-quadruplex streptavidin aptamer containing nine 5-ITZ-dUTPs which has a high affinity to the target is discovered. This aptamer shows 6.5-fold and 9-fold higher binding affinities than the appropriate control sequences which contain non-halogen bearing nucleotides (5-propargylamino-prototriazole-dU or canonical dT). Further studies to demonstrate halogen bonding in aptamer-target interaction are required to confirm this as the first example of halogen bonding in aptamer-protein interactions.